2001
DOI: 10.1128/iai.69.3.1625-1629.2001
|View full text |Cite
|
Sign up to set email alerts
|

Implication of the Structure of theHelicobacter pylori cagPathogenicity Island in Induction of Interleukin-8 Secretion

Abstract: Helicobacter pylori virulence is associated with the presence of the cag pathogenicity island (PAI). The cag PAI is involved in the ability to induce interleukin-8 (IL-8) secretion by human cells, which is implicated in the inflammatory response of the gastric mucosa to H. pylori infection. The aim of this study was to determine whether the genetic structure of the cag PAI is conserved and whether it is linked to IL-8 induction ability. Detection of specific markers (cagA, picB, cag13-cag14, virD4, and IS605) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 28 publications
2
46
1
Order By: Relevance
“…Fifty per cent of strains from West India are devoid of the entire island of genes (Kauser et al, 2004), 32 % in France (Audibert et al, 2001), 9 % in Sweden (Nilsson et al, 2003) and the USA (Hsu et al, 2002) and 1 % in Japan (Ikenoue et al, 2001). In the present report, none of the strains showed complete deletion of the cagPAI genes.…”
Section: Amplification Of Cagpai Genesmentioning
confidence: 54%
“…Fifty per cent of strains from West India are devoid of the entire island of genes (Kauser et al, 2004), 32 % in France (Audibert et al, 2001), 9 % in Sweden (Nilsson et al, 2003) and the USA (Hsu et al, 2002) and 1 % in Japan (Ikenoue et al, 2001). In the present report, none of the strains showed complete deletion of the cagPAI genes.…”
Section: Amplification Of Cagpai Genesmentioning
confidence: 54%
“…Correlation between integrity of cagPAI, types of EPIYA motifs, and disease outcome was confirmed by several studies (24,(38)(39)(40)(41)(42). However, there are studies that reported contrary results (43)(44)(45). Variation in H. pylori genome from various areas and presence of polymorphisms in different gene loci of cagPAI could be main causes of the differences among the studies.…”
Section: Discussionmentioning
confidence: 76%
“…H. pylori microevolution can determine loss of all or part of the cagPAI [23]. In Japanese and French studies, cagE was found to be a better marker for the presence of cagPAI than cagA [36,37]. We did not perform detection of cagPAI empty site, and this is a limitation of our work.…”
Section: Discussionmentioning
confidence: 89%